Interactivity in online chat : conversational contingency and response latency in computer-mediated communication - Shin, Wonsun (2019)
In dyadic online chats with customers, agents commonly employ scripted responses and converse with several customers simultaneously in order to enhance efficiency. These techniques, however, can affect dimensions of interactivity—conversational contingency and response latency—undermining interpersonal assessments, satisfaction, and organizations’ relationships with customers. This research incorporates aspects of interactivity to the social information processing (SIP) theory of computer-mediated communication, that addresses conversational behaviors that affect interpersonal relations in the absence of nonverbal cues. In a 2 × 2 between-subjects experiment, observers watched one of four versions of a dialogue between a customer and sales support agent, which differed with respect to the agent’s response latency and conversational contingency. Results confirmed deleterious effects of non-contingency on outcomes. Contingency moderated latency effects. Mediation analyses showed indirect effects of contingency via interpersonal judgments on organization/customer relations. Implications for a more comprehensive approach to SIP conclude the study.